EVALUASI METODE PEMBAYARAN CASH ON DELIVERY (COD) di PLATFORM SHOPEE PADA PRODUK KOSMETIK - Ayu Fera Wati; Uswatun Chasanah (Jurnal Riset Manajemen Akuntansi Indonesia, 2026)
This study employs a qualitative method to analyze the implementation of the cash on delivery payment method for cosmetic product transactions on the shopee platform. Data collection was carried out using in depth interviews with three informants consisting of a consumer, a seller, and expedition courier. This research aims to analyze the implementation of the cash on delivery payment method in cosmetic product transactions on the shopee platform and to identify the perceptions of consumers, seller, and couriers toward this payment method. The data were analyzed using the Miles, Huberman, and Saldana (2014) interactive analysis model which includes the stages of data reduction, data display, and conclusion drawing. The findingindicate that the cash on delivery payment method provides convenience and a sense of security for consumers, as it allows them to inspect the product before making a payment. For sallers, this method effectively increases sales because many consumers are more interested in shopping using the cash on delivery method. However, sellers face challenges such as the risk of product rejection and delayed payments. Meanwhile, for couriers, the cash on delivery method adds to their workload, as they must handle cash transactions and deal with order cancellations at the delivery point. In conclusion, implementation of the cash on delivery payment method on shopee has a positive impact on increasing consumer trust and expanding market reach,however, it requires good risk management to mitigate potential losses for sallers and couriers.